2016
DOI: 10.1038/srep38447
|View full text |Cite
|
Sign up to set email alerts
|

Renal Denervation Improves the Baroreflex and GABA System in Chronic Kidney Disease-induced Hypertension

Abstract: Hypertensive rats with chronic kidney disease (CKD) exhibit enhanced gamma-aminobutyric acid (GABA) B receptor function and regulation within the nucleus tractus solitarii (NTS). For CKD with hypertension, renal denervation (RD) interrupts the afferent renal sympathetic nerves, which are connecting to the NTS. The objective of the present study was to investigate how RD improves CKD-induced hypertension. Rats underwent 5/6 nephrectomy for 8 weeks, which induced CKD and hypertension. RD was induced by applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…GABA has been reported to reduce cerebrospinal fluid in hypertensive CKD rats, and oral administration of a GABA analog increased periphery GABA levels and decreased blood pressure [28]. Consistent with this animal research, we found that GABA levels were negative correlated with blood pressure in CKD patients, suggesting that GABA supplementation may be beneficial in CKD patients with hypertension.…”
Section: Discussionsupporting
confidence: 89%
“…GABA has been reported to reduce cerebrospinal fluid in hypertensive CKD rats, and oral administration of a GABA analog increased periphery GABA levels and decreased blood pressure [28]. Consistent with this animal research, we found that GABA levels were negative correlated with blood pressure in CKD patients, suggesting that GABA supplementation may be beneficial in CKD patients with hypertension.…”
Section: Discussionsupporting
confidence: 89%
“…It has been suggested that arterial baroreflex is involved in the long-term control of BP [ 30 ]. Several studies have shown that the sensitivity of the baroreflex is diminished in several forms of hypertension [ 22 , 31 , 32 ]. In addition, patients with baroreflex failure suffer from a volatile hypertension with sympathetic nerve activity increased for years [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in patients with renovascular hypertension, restoration of renal perfusion reduces muscle sympathetic nerve activity and blood pressure (Miyajima et al, 1991 ) and renal nerve ablation can reduce blood pressure and muscle sympathetic nerve activity in some patients with resistant hypertension (Hering et al, 2014 ). Finally, given the change in set-point of sympathetic activity and blood pressure it is perhaps not surprising that the baroreceptor reflex is reset and gain improved following renal denervation in a rat model of chronic kidney disease (Chen et al, 2016 ).…”
Section: Hypoxia Afferent Nerve Activation/sensitization and Hypertementioning
confidence: 99%